FAKTOR-FAKTOR YANG MEMENGARUHI PENGAMBILAN KEPUTUSAN PETANI DALAM MEMILIH POLA PEREMAJAAN KELAPA SAWIT DI KEBUN PLASMA PT INTI INDOSAWIT SUBUR - Ayat Khumaini; Zulkifli Alamsyah; Rozaina Ningsih (Agros Journal of Agriculture Science, 2024)
The purpose of this research is to 1) determine the pattern of implementation of rejuvenation in PT's plasma plantations. Inti Indosawit Subur Kebun Muara Bulian, 2) analyzing the factors that influence farmers' decision making in choosing a rejuvenation pattern for oil palm plants, 3) analyzing the most dominant factors in farmers' decision making in choosing a rejuvenation pattern. The data used is primary data, research starts from December 2022 to August 2023, using quantitative descriptive methods, binary logistic regression data analysis. The research results show that the pattern of implementing oil palm rejuvenation consists of an independent pattern of 37.94%, namely 313 farmers or 776 hectares and a partnership pattern of 62.06%, namely 512 farmers or 1,348 hectares. The condition of gardens rejuvenated using an independent pattern is generally heterogeneous. Factors that significantly influence farmers' decision making are age, whether or not there is alternative income, the average amount of alternative income per month, number of dependents, land area, plantation management status, support from government extension workers and support from company extension workers. The most dominant factor influencing the choice of partnership pattern palm oil rejuvenation is the support of company extension workers.